Managing Customer Citizenship Behavior in Aviation Sector Through Relational Benefits: Mediating Role of Relationship Quality - Hassan, Shahzad; Suki, Norazah Mohd (Frontiers in Psychology, 2022)
The aim of the research is to investigate the mediating role of relationship quality in the relationship of relational benefits and customer citizenship behavior. Data were gathered through systematic sampling from 334 passengers. Survey technique was used to collect the data from respondents from multiple airports. Data were analyzed through partial least square structural equation modeling (PLS-SEM) using SmartPLS 3.3. The results of the study reveal that altruistic benefits, confidence and self-expression benefits has positive relationship with relationship quality while socialization benefits have non-significant relationship with relationship quality. Same as relationship quality mediates the relationship between altruistic benefits, confidence and self-expression benefits and customer citizenship behavior while relationship quality does not mediate the relationship between socialization benefits and customer citizenship behavior. This study uncovers the relational benefits and its role in generation of customer citizenship behavior in aviation sector and the role of relationship quality that could help managers to cultivate the benefits of customer citizenship behaviors.